City of Ember - Goetzman, Gary, 1952-; Hanks, Tom.; Shareshian, Steven; Thompson, Caroline, 1956-; Kenan, Gil.; Ronan, Saoirse, 1994-; Treadaway, Harry, 1984-; Robbins, Tim, 1958-; Murray, Bill, 1950 Sept. 21-; Landau, Martin, 1928-; Place, Mary Kay.; Jones, Toby, 1967-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
For centuries, the residents of the underground City of Ember have flourished in an amazing world of glittering lights and quiet contentment. But when the City's massive power generator begins to fail, the streetlamps fade - along with the hopes of the townspeople. Now it will be up to two courageous teenagers to follow a trail of clues left by the ancient builders to find the way out of Ember before their world is plunged into complete darkness.
Side A. City of Ember (full screen feature) -- Side B. City of Ember (widescreen feature).
Based on the book "The City of Ember" by Jeanne DuPrau.
Director of photography, Xavier Přez Grobet ; production designer, Martin Laing ; editors, Adam P. Scott, Zach Staenberg ; costume designer, Ruth Myers ; music, Andrew Lockington.
Saoirse Ronan, Harry Treadaway, Tim Robbins, Bill Murray, Martin Landau, Mary Kay Place, Toby Jones.
MPAA rating: PG; for mild peril and some thematic elements.
DVD, full screen (1.33:1) and widescreen (2.35:1); Dolby Digital 5.1 surround, Dolby Digital surround, double- sided.
English (Dolby 5.1), French (Dolby surround) or Spanish (Dolby surround) dialogue, English or Spanish subtitles; closed-captioned for the hearing impaired.
Keywords: Technology and civilization -- Juvenile drama; Civilization, Subterranean -- Juvenile drama; Electric generators -- Juvenile drama; Teenagers -- Conduct of life -- Juvenile drama; Architects and builders -- Juvenile drama; Occupations -- Juvenile drama; Film adaptations; Action and adventure films; Fantasy films